Effect of Artificial Defects on the Very High Cycle Fatigue Behavior of 316L Stainless Steel - Zhihong Xiong; Takashi Naoe; Masatoshi Futakawa (Metals, 2019)
Widely used for structural materials in nuclear engineering, 316L austenitic stainless steel undergoes very high cycle fatigue (VHCF) throughout its service life. Since defects caused by service conditions are unavoidable in many engineering components during service life, the effects should be properly understood. In the present study, the effect of surface defects on the VHCF behavior were investigated on solution annealed (SA) and cold-worked (CW) 316L. Surface defects were artificially created using indentation. The VHCF test was conducted using an ultrasonic fatigue testing system. The results showed that the fatigue crack initiation was independent of the indent with the applied range of depth in this research. Furthermore, the critical depth of the indent was evaluated based on an empirical formula (Murakami’s model). In the case of SA 316L, the VHCF strength was not affected when the indent depth was less than 40 μm, which is consistent with the value obtained from the empirical formula. In the case of 20% CW 316L, the VHCF strength was not affected when the indent depth was less than 80 μm. The experimental results, i.e., the critical depth of the indent, were much larger than the results obtained from the empirical formula, and might have been caused by the plastic deformation, residual stress, and probable deformation-induced martensite transition around the indent.